ANALISIS SIFAT MEKANIK KOMPOSIT DIPERKUAT SERAT PINANG MENGGUNAKAN METODE PENGUJIAN BENDING STATIK - Muhammad Arifin; Fadly Ahmad Kurniawan Nasution (Universitas Harapan Medan, 2019)
This study aims to analyze the mechanical properties of areca nut fiber reinforced composites using static bending testing methods. Areca nut fiber reinforced composites are materials that show potential as an attractive alternative in engineering applications and natural fiber-based materials. Static bending testing methods are used to evaluate the modulus of elasticity, tensile strength, flexural strength, and ductility of composites. At the sample preparation stage, areca nut fibers are well arranged in a resin matrix to form a composite sample. The test is performed by applying a load on the midpoint of the sample gradually until a significant fracture or deformation occurs. During the test, the strain, force, and change in shape of the sample are measured. The test results show that areca nut fiber reinforced composites have significant values of modulus of elasticity, tensile strength, flexural strength, and ductility. Factors such as fiber orientation, fiber-matrix composition, and interactions between fibers and matrices can affect the mechanical characteristics of composites. This research provides a better understanding of the mechanical properties of areca nut fiber reinforced composites, which can be used for the development and application of such materials. The results of this study can also be used as a basis for comparison with other fiber-reinforced composites or other materials used in similar applications.